KEMAMPUAN GURU DALAM MENGAJAR MELALUI WORKSHOP MODEL KOOPERATIF DI SDN 016 PULAU KECIL - Ermansyah Ermansyah (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
This research is motivated by the ability of teachers to implement learning has not shown maximum results. This is due to the lack of the teacher's ability to apply the learning model and the use of learning models that are not yet in accordance with the students' creative characteristics and classroom situation. The purpose of this study is to improve the ability of teachers to teach. In this case the researcher tries to intensify the implementation of the cooperative model workshop in an effort to minimize weaknesses in carrying out the learning process. This research was conducted in two cycles, the steps in each cycle consisted of planning, implementing actions, observing, and reflecting. The results showed, in the aspect of teacher attendance in the first cycle, only 5 people attended the workshop with a percentage of 83%, after the second cycle had increased to 100%. In the aspect of readiness of teacher materials in participating in the workshop as many as 4 people or 67% in the prepared category, after the second cycle it was increased to 100% ready category. The readiness aspect of laptops as much as 50% is ready and after the second cycle has increased to 83% the teacher is ready. The results of the teacher teaching assessment using the cooperative model in the first cycle, the average teacher gets a score of 67.8 in the good category, after the second cycle, the teacher's teaching assessment results increase to 86.5 in the excellent category. Based on the results of the above research, researchers can conclude that by applying the workshop cooperative learning models can improve the ability of teachers to teach in 012 Small Island Elementary Schools